THE DEVELOPMENT OF STUDENTS' SOCIAL SKILLS IN FOREIGN LANGUAGE CLASSES (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
This article describes the significance of social competence within the framework of essential competencies in education, as well as detailing the methods, circumstances, and strategies for cultivating social competence during foreign language classes through the use of competency-based teaching techniques.